Bilateral Submandibular Gland Aplasia: A Case Report and Review of the Literature - Akyol, Muammer; Cicekci, Mehtap; Duzer, Sertac (Puerto Rico Health Sciences Journal, 2022)
The congenital absence of major salivary glands, particularly the submandibular gland, is a rare condition. Although the etiology of aplasia is unknown, it is thought to occur owing to defects that emerge during early fetal development. Agenesis of 1 or more of the major salivary glands may occur alone or in association with other congenital anomalies. Very few cases of bilateral submandibular gland aplasia have been reported in the literature. Patients with this condition can be either symptomatic or asymptomatic. Due to the probability of there being additional anomalies, patients and their families should be carefully evaluated. We present the ultrasound and computed tomography findings for a case of bilateral submandibular gland aplasia that was detected incidentally. A review of the literature on major salivary gland aplasia was also conducted.